Kualitas Hidup Pasien Tuberkulosis Paru dengan Stigma Diri - Sari, Yunita (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2019)
Pulmonary tuberculosis (TB) is a chronic disease that can bring about the sufferer's self-stigma and also affect his quality of life. A number of studies report that living with TB has a negative influence on the quality of life of sufferers even with or without self-stigma. The purpose of this study was to identify the quality of life of TB patients who experienced self-stigma. This research is a descriptive study, sample were 31 pulmonary TB patients. Data was collected using a questionnaire. Data analyzed by using frequency distribution and percentage. The researcher first screened TB patients who experienced self-stigma. The results showed that 25 people (80.64%) respondents experienced mild self-stigma. A total of 9 respondents (36%) had a quality of life score in the good category and as many as 16 respondents (64%) had enough category with an average quality of life score is 56.57. While respondents who had moderate self-stigma were 6 people (19.36%) with a good quality of life score was 1 person (16.67%) and enough category quality of life score were 5 people (83.33%) with an average quality of life score is 49.92. Keywords: quality of life, self stigma, pulmonary tuberculosis